Open pangenome of Lactococcus lactis generated by a combination of metagenome-assembled genomes and isolate genomes - Zhai, Yiting; Wei, Chaochun (Frontiers in Microbiology, 2022)
Lactococcus lactis (L. lactis) is a well isolated and cultured lactic acid bacterium, but if utilizing the isolate genomes alone, the genome-based analysis of this taxon would be incomplete, because there are still uncultured strains in some ecological niches. In this study, we recovered 93 high-quality metagenome-assembled genomes (MAGs) of L. lactis from food and human gut metagenomes with a culture-independent method. We then constructed a unified genome catalog of L. lactis by integrating these MAGs with 70 publicly available isolated genomes. Having this comprehensive resource, we assessed the genomic diversity and phylogenetic relationships to further explore the genetic and functional properties of L. lactis. An open pangenome of L. lactis was generated using our genome catalog, consisting of 13,066 genes in total, from which 5,448 genes were not identified in the isolate genomes. The core genome-based phylogenetic analysis showed that L. lactis strains we collected were separated into two main subclades corresponding to two subspecies, with some uncultured phylogenetic lineages discovered. The species disparity was also indicated in PCA analysis based on accessory genes of our pangenome. These various analyzes shed further light on unexpectedly high diversity within the taxon at both genome and gene levels and gave clues about its population structure and evolution. Lactococcus lactis has a long history of safe use in food fermentations and is considered as one of the important probiotic microorganisms. Obtaining the complete genetic information of L. lactis is important to the food and health industry. However, it can naturally inhabit many environments other than dairy products, including drain water and human gut samples. Here we presented an open pan-genome of L. lactis constructed from 163 high-quality genomes obtained from various environments, including MAGs recovered from environmental metagenomes and isolate genomes. This study expanded the genetic information of L. lactis about one third, including more than 5,000 novel genes found in uncultured strains. This more complete gene repertoire of L. lactis is crucial to further understanding the genetic and functional properties. These properties may be harnessed to impart additional value to dairy fermentation or other industries.